Economic burden of chronic obstructive pulmonary disease patients and its influencing factors in rural Yunnan province: a population-based study - Lan LIU; Xu-ming WANG; Yi MO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the economic burden of patients with chronic obstructive pulmonary disease (COPD) and its influencing factors in rural regions of Yunnan province and to provide evidence for formulating health policies and measures to reduce the economic burden. MethodsFace-to-face interview with a self-designed questionnaire and lung function test were conducted among 7 704 permanent residents at ages of 35 years and above recruited using stratified multistage random sampling in rural regions of Yunnan province from November 2020 to November 2021. Both direct and indirect cost of COPD patients were estimated and the influencing factors of the cost were analyzed with structural equation modeling. ResultsAmong the 7 572 participants with complete information, 954 COPD patients were diagnosed, with a prevalence rate of 12.6%. The estimated average annual COPD-related expenditure per patient was 5 787.2 Yuan (RMB); in which, 98.50% (5 700.5 Yuan) and 1.50% (87.2 Yuan) was direct and indirect cost. For the direct expenditure, the cost of hospitalization, outpatient service, medication, and accommodation/transportation were 3 020.7, 1 189.1, 141 8.6, and 72.1 Yuan. The results of structural equation model analysis indicated that the COPD patients' economic burden was associated with the condition of hospitalization, frequency of outpatient visits within one year and the impact of the disease on patients' life and work, with the standardized regression coefficient of 0.43, 0.36 and 0.27. The standardized regression coefficient for the length of hospital stay and the type of medical institution were 0.41 and 0.40; while the standardized regression coefficient for the impact of the disease on daily work, housework and daily life was 0.26, 0.23 and 0.23, respectively. ConclusionThe economic burden of rural COPD patients is relatively high in Yunnan province. The study results suggest that early diagnosis and treatment of the disease, reducing duration of hospitalization and the level of medical institution providing hospitalization service could alleviate the economic burden of the rural COPD patients.